Morphometric changes associated with sex and development in the Malpighian tubules of Aedes aegypti - De Sousa, Rita De Cássia [UNESP]; Bicudo, Hermione E. M. C. [UNESP] (My University, 2000)
The Malpighian tubules of Aedes aegypti showed significant differences in their diameters between male and female larvae, male and female pupae, male larvae and male adults and male pupae and male adults. In every case, female values were greater than in males. Measurements of mean nuclear areas of the principal and stellate cells from Malpighian tubules, taken in males and females during development, showed that this parameter in both types of cell was significantly greater in females than in male larvae, pupae and adult stages. In males, significant differences between developmental stages were observed only in comparison with the nuclear area of larvae and adults in the principal cells, but in females, every comparison between stages showed significant differences except between pupae and adults in stellate cells. The frequency distribution of nuclear area values, in development, for male stellate and principal cells, were mostly concentrated in the first seven classes among the 30 classes considered in every stage, while for females, the frequency dropped drastically in the same classes from larvae to pupae and adults, moving to classes of higher values. Considering the importance of Malpighian tubules in insect physiology, the meaning of the differences detected are discussed on the basis of different metabolic levels, between sexes and developmental stages.
Keywords: Aedes aegypti; Malpighian tubules; Morphology